Externalidades económicas en el sector terciario por la inversión pública en la creación y mejoramiento de los servicios turísticos en la zona monumental de la ciudad de Iquitos - Loreto 2022 - Zunini Inga, Frank Alfonzo Thomas (2024)
The purpose of the study is to determine the economic externalities of the urban public works “Creation and improvement of tourist services in the monumental area of the city of Iquitos. It is a non-experimental, descriptive, analytical, cross-sectional study. The primary information was obtained from a structured interview with people whose homes and/or businesses are in the area of project intervention. The inferential analysis was performed using the Rho Spearman test. The presence of externalities is evident that despite it being a public work, those involved expressed their disagreement with its execution due to the high uncertainty in the impacts it would produce in the short term. They recognize the negative impact or externality on their commercial activities, with the closure of businesses, they emphasize the need to implement support measures through subsidies. They show a decrease in the influx of visitors, national and foreign tourists, but they consider that the work will have a positive impact on tourist activity in the long term. They recognize that the ability to provide quality services to visitors has had a negative impact. Likewise, entertainment and leisure businesses suffered a great negative impact, they were forced to close and/or relocate temporarily. modify the hours of service to the public due to an increase in criminal activity, due to the influx of undesirable people in the intervention area. It recognizes very significant economic losses in local businesses in the short term, which has increased due to the delay in the completion of the work, creating discomfort in the population. But it must also be recognized that the completion of the work, in the medium and long term, will be capable of generating positive externalities for the families and businesses of the monumental area of Iquitos. For its part, statistical evidence shows that those involved who perceived a greater negative economic impact on their businesses are those who also least agreed with the execution of the work. Therefore, the null hypothesis is rejected and the alternative is accepted.